In-situ relative humidity monitoring and phase-change flow simulation for elucidating dynamic mechanism of water management faults in PEMFC - Runze Liu; Xin Cai; Ruizhe Feng; Yunyang Ma; Andreas Friedrich; Rui Lin (Chemical Engineering Journal, 2026)

Damage assessment of CFST columns internally strengthened with I-shaped CFRP under combined collision and explosion loads - Guochang Li; Jialong Wang; Xiao Li; Yue Zhou; Runze Liu; Rikai Lin (Engineering Structures, 2026)

Data-driven discovery of high-performance surface passivators for efficient and stable perovskite solar cells - Feiyi Zhou; Zeyu Wang; Shangshang Zhao; Xu Zhang; Qingyue Guo; Runze Dai; Fanxiang Meng; Huajie Lyu; Jun Wan; Yi Dong; Zhe Jin; Shanqing Yu; et al. (Chemical Engineering Journal, 2026)

A two-stage liquefaction approach based on the bond cleavage characteristics and interactive behavior of vitrinite and inertinite in Shangwan coal - Yuanzhe Wang; Lei Shi; Zhenyu Liu; Tong Zhao; Lin Lin; Qingya Liu; Yuxin Yan; Jianli Wang; Shansong Gao; Runze Zhao (Fuel, 2026)

Can 3D printed food affect consumer self-expressiveness and sharing intention? The lens from the value-attitude-behavior model - Zhengan Zhu; C. Michael Hall; Runze Mao; Feifei Lin (International Journal of Gastronomy and Food Science, 2026)

Unveiling the choroidal immune landscape revealed interferon-gamma and TNF-alpha as novel therapeutic targets in dry AMD - Lin Ye; Tujing Zhao; Huaping Tian; Runze Li; Zheng Li; Hongjing Li; Ruilin Liao; Junlan Chuan; Haojue Xu; Liang Zou; Chao Qu; Yi Shi; et al. (Science China Life Sciences, 2026)

Exploring the role of VAV2 rare variants in primary open-angle glaucoma: genetic insights and pathophysiological mechanisms - Runze Li; Yuhong Chen; Shanshan Zhang; Lin Ye; Huaping Tian; Zheng Li; Wentao Wang; Hongjing Li; Ruilin Liao; Haojue Xu; Junlan Chuan; Chao Qu; et al. (Science China Life Sciences, 2026)

Superconducting phase interference effect in momentum space - Bo Zhan; Qiang Gao; Runze Chi; Yiwen Chen; Lin Zhao; Dingshun Lv; Xingjiang Zhou; Tao Xiang (Science Bulletin, 2025)

Nitrogen fertilization management is required for soil phosphorus mobilization by phoD-harboring bacterial community assembly and pqqC-harboring bacterial keystone taxa - Lin YANG; Runze WANG; Jingwei SHI; Rui WANG; Shengli GUO (Pedosphere, 2025)

The chemical basis of aroma/taste and color formation in green tea infusion during cold brewing revealed by metabolomics analysis - Chen Yang; Zhaojun Wang; Minghui Xu; Kaikai Wei; Qianying Dai; Xiaochun Wan; OiPo Leong; Runze Lin; Chuanjian Cui; Ruyan Hou (Food Chemistry, 2025)

The research on the evaluation framework and application of urban three-dimensional (aboveground and underground) regeneration sensitivity——Taking Kunshan Old City in China as an example - Kunyang Li; Jizhong Shao; Runze Lin; Guan Liu; Yu Zhang; Minge Yang (Tunnelling and Underground Space Technology, 2025)

Freeze-dried cellulose-based aerogel with unidirectional pore structure for anionic dyes and oils adsorption - Shuo Zhang; Yanqiu Pan; Qi Fan; Wei Wang; Runze Lin (Chemical Engineering Journal, 2025)

Modeling of wave-induced drift based on stepwise parameter calibration - Kui Zhu; Xueyao Chen; Lin Mu; Dingfeng Yu; Runze Yu; Zhaolong Sun; Tong Zhou (Frontiers in Marine Science, 2025)
The motion of waves in water causes the slow movement of drifting sea targets—a phenomenon usually ignored in target-drift prediction models for maritime search and rescue (SAR). This study examined the wave-induced drift’s influence on field-observation experiments involving two common, differently sized SAR targets—an offshore fishing vessel (OFV) and a person in the water (PIW)—using parameter stepwise calibration and machine-learning (ML) methods. The sample of wave-induced drift velocity was obtained by gradually separating current-induced (CI) drift’s and wind-induced (WI) drift’s influence from the target-drift velocity using the least-square method and AP98 model. A force analysis method and three ML methods, long short-term memory (LSTM), back-propagation (BP) neural network, and random forest (RF), were used to fit the wave-induced drift velocity by combining eight different parameter schemes. Finally, the drift trajectories considering the influence of waves were fitted and verified based on 2 independent samples respectively. Compared with the force analysis method, the accuracy of the ML methods in the verification test was higher. In addition, the results show that for OFVs, considering wave-induced drift’s influence in the ensemble-trajectory prediction could improve the simulation accuracy. However, for a PIW, no significant improvement was observed. This result also indicates that wave-induced drift may not be simply ignored in large SAR targets’ drift prediction.

Effect of wall slip of CO2-in-water foams on enhanced oil recovery - Biao Xu; Jiuqing Li; Lin Zhu; Junyan Xu; Runze Wang; Shun Li; Jiajia Fu; Jingyi Yang; Tao Liu (Chemical Engineering Journal, 2025)

Responses of winter wheat yield and soil organic carbon to long-term (1990–2021) fertilization regimes under inter-annual weather variation in the Loess Plateau - Panxin Zhang; Victor O. Sadras; Runze Zhang; Lin Liu; Xueyun Yang; Benhua Sun; Changlu Hu; Hu Xu; Shulan Zhang (European Journal of Agronomy, 2024)

Comparative transcriptome analysis provides insights into the resistance regulation mechanism and inhibitory effect of fungicide phenamacril in Fusarium asiaticum - Zhitian Zheng; Huaqi Liu; Xiao Luo; Runze Liu; Alexander Dumbi Joe; Haolin Li; Haiyan Sun; Yanling Lin; Yanzhong Li; Yunpeng Wang (Pesticide Biochemistry and Physiology, 2024)

Manure replacing synthetic fertilizer improves crop yield sustainability and reduces carbon footprint under winter wheat–summer maize cropping system - Jincan Niu; Qudsia Saeed; Wenning Wang; Runze Zhang; Lin Liu; Fenglian Lv; Jiaxing Xu; Yan Han; Panxin Zhang; Changlu Hu; Hu Xu; Benhua Sun; et al. (Journal of Environmental Management, 2024)

Biocontrol activity of an endophytic Alternaria alternata Aa-Lcht against apple Valsa canker - Yanting He; Runze Tian; Chengyu Gao; Lin Ji; Xiao Liu; Hao Feng; Lili Huang (Pesticide Biochemistry and Physiology, 2024)

Effects of microplastic properties and dissolved organic matter on phosphorus availability in soil and aqueous mediums - Runze Wang; Lin Yang; Miaomiao Guo; Xiaohua Lin; Rui Wang; Shengli Guo (Environmental Pollution, 2024)

DeepFlame: A deep learning empowered open-source platform for reacting flow simulations - Runze Mao; Minqi Lin; Yan Zhang; Tianhan Zhang; Zhi-Qin John Xu; Zhi X. Chen (Computer Physics Communications, 2023)

Carboxylated cellulose-based aerogel with cellular pores prepared by stir freezing for cationic dye adsorption - Shuo Zhang; Yanqiu Pan; Wei Wang; Runze Lin; Xuewu Liu (Process Safety and Environmental Protection, 2023)

Probabilistic modelling of surface drift prediction in marine disasters based on the NN–GA and ARMA model - Kui Zhu; Lin Mu; Runze Yu; Xiaoyu Xia; Haiwen Tu (Ocean Engineering, 2023)

Changes in fungal diversity and key-stone taxa along soil-eroding catena - Runze Wang; Lin Yang; Xin Gao; Shengli Guo; Rui Wang (Applied Soil Ecology, 2023)

Deep Sc-RNA sequencing decoding the molecular dynamic architecture of the human retina - Lulin Huang; Runze Li; Lin Ye; Shanshan Zhang; Huaping Tian; Mingyan Du; Chao Qu; Shujin Li; Jie Li; Mu Yang; Biao Wu; Ran Chen; et al. (Science China Life Sciences, 2023)